Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1086/315232
|View full text |Cite
|
Sign up to set email alerts
|

Type Specificity and Significance of Different Isotypes of Serum Antibodies to Human Papillomavirus Capsids

Abstract: Isotype-specific serum antibody responses against human papillomavirus (HPV) type 16 were evaluated by use of cross-sectional, prospective, and population-based seroepidemiologic studies. IgG1 and IgA were the most abundant isotypes. No sample contained IgG2, and <25 samples contained IgG3 or IgM. Total IgG, IgA, and IgG1 were HPV type specific and were associated with HPV-16 DNA (odds ratios [ORs], 5.4, 5.0, and 5.9, respectively; P<.001) but not with other HPV DNA (ORs, 1.2, 1.2, and 0.8, respectively; P val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 30 publications
3
14
0
2
Order By: Relevance
“…A number of studies have supported the use of HPV-16 VLP as a biomarker of past HPV exposure, with moderate associations between HPV seropositivity and cervical cancer Dillner et al, 1996). As previously reported, the magnitude of association between seropositivity and cervical cancer in this study were 2 -3-fold compared to HPV seronegative women Chua et al, 1996;Dillner et al, 1996Dillner et al, , 1997Wideroff et al, 1996;Wang et al, 2000;Sigstad et al, 2002). Our stratified analyses clearly demonstrated that HPV DNApositive women had the highest levels of risk for CIN3/cancer; for HPV-18 and -31, risk for CIN3/cancer was highest for women both HPV DNA-and sero-positive followed by women DNA-positive only.…”
Section: Discussionsupporting
confidence: 79%
“…A number of studies have supported the use of HPV-16 VLP as a biomarker of past HPV exposure, with moderate associations between HPV seropositivity and cervical cancer Dillner et al, 1996). As previously reported, the magnitude of association between seropositivity and cervical cancer in this study were 2 -3-fold compared to HPV seronegative women Chua et al, 1996;Dillner et al, 1996Dillner et al, , 1997Wideroff et al, 1996;Wang et al, 2000;Sigstad et al, 2002). Our stratified analyses clearly demonstrated that HPV DNApositive women had the highest levels of risk for CIN3/cancer; for HPV-18 and -31, risk for CIN3/cancer was highest for women both HPV DNA-and sero-positive followed by women DNA-positive only.…”
Section: Discussionsupporting
confidence: 79%
“…HPV seropositivity was previously found to be linked with several characteristics, mainly sexual activity indicators such as lifetime number of sexual partners, HSV-2 seropositivity, and marital status, as well as to oral contraceptive use and smoking (5,8,14,17,23,(35)(36)(37)(38)(39)(40). In the present study, a clear dose-response relationship was observed for both HPV16 and HPV18 seropositivity with lifetime number of sexual partners, the most important risk factor for cervical HPV DNA prevalence in the same populations (41).…”
Section: Discussionsupporting
confidence: 64%
“…HPV seroprevalence doubled to 25% among sexually active women in this study, and this increase was seen independently for each of the seven HPV types tested. Although a strong increase in HPV seropositivity with increasing number of sexual partners has been widely reported (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), far fewer studies have allowed a comparison with women reporting to be nonsexually active (6,29).…”
Section: Discussionmentioning
confidence: 99%